Interleukin‐15 receptor α expression in inflammatory bowel disease patients before and after normalization of inflammation with infliximab. Issue 1 (13th December 2012) - Perrier, Clémentine; Arijs, Ingrid; Staelens, Dominiek; Breynaert, Christine; Cleynen, Isabelle; Covens, Kris; Ferrante, Marc; Van, Gert; Vermeire, Séverine; de, Gert; Schuit, Frans; Rutgeerts, Paul; et al.
Summary Interleukin‐15 (IL‐15) is a pro‐inflammatory cytokine thought to contribute to the inflammation in inflammatory bowel diseases (IBD). The specific receptor chain IL‐15Rα can be expressed as a transmembranous signalling receptor, or can be cleaved by a disintegrin and metalloprotease domain 17 (ADAM17) into a neutralizing, soluble receptor (sIL‐15Rα). The aim of this study is to evaluate the expression of IL‐15Rα in ulcerative colitis (UC) and Crohn's disease (CD) patients before and after infliximab (IFX) therapy. Gene expression of IL‐15Rα, IL‐15 and ADAM17 was measured at the mRNA level by quantitative reverse transcription‐PCR in mucosal biopsies harvested before and after first IFX therapy. Concentrations of sIL‐15Rα were measured in sera of patients by ELISA and IL‐15Rα protein was localized in the gut by immunohistochemistry and immunofluorescence. Mucosal expression of IL‐15Rα is increased in UC and CD patients compared with controls and it remains elevated after IFX therapy in both responder and non‐responder patients. The concentration of sIL‐15Rα in serum is also increased in UC patients when compared with controls and does not differ between responders and non‐responders either before or after IFX. CD patients have levels of sIL‐15Rα comparable to healthy controls before and after therapy. In mucosal tissues, IL‐15Rα+ cells closely resemble activated memory B cells with a pre‐plasmablastic phenotype. To conclude, IBD patients have an increased expression of IL‐15Rα mRNA in the mucosa. Expression is localized in B cells, suggesting that IL‐15 regulates B‐cell functions during bowel inflammation. No change in release of sIL‐15Rα is observed in patients treated with IFX.